ADAPTATION OF TECHNOLOGICAL PRODUCTS FROM UKRAINE TO FOREIGN MARKETS - Ohinok, Solomiia; Prykhodko, Iryna (Український економічний часопис, 2024)
Introduction. In the context of rapid technological transformation and economic globalization, the adaptation of technological products to foreign markets becomes critically important for the success of enterprises. Ukraine, possessing significant potential in the field of technology, faces the challenge of effectively penetrating foreign markets with its products. The adaptation of Ukrainian technological products requires studying and understanding the specifics and demands of international consumers, as well as considering intercultural differences and regulatory constraints. Research on this topic will contribute to enhancing the competitiveness of Ukrainian enterprises on the international stage, promoting export growth, and attracting foreign investments, which are of great significance for the country's economic development. Therefore, this topic is relevant and important for the further development of Ukraine's technological sector and support of its position in global markets. Purpose. This article aims to explore the process of adapting Ukrainian technological products for successful entry into foreign markets. Given the intensifying globalization and competitive environment, adaptation is pivotal for ensuring the competitiveness of Ukrainian companies on the international stage. Methods. The research examines technical, cultural, and strategic dimensions of product adaptation, including the analysis of foreign market needs, implementing necessary product modifications, and navigating local regulatory and cultural nuances. Additionally, it investigates best practices and strategies for effective adaptation that Ukrainian enterprises can leverage. The article explores the process of adapting Ukrainian technological products for successful entry into foreign markets. Given the increasing globalization and competitive environment, the adaptation of technological solutions is a key strategy to ensure the competitiveness of Ukrainian companies internationally. The article examines technical, cultural, and strategic aspects of adaptation, such as studying the needs and requirements of foreign markets, implementing appropriate changes in the product, and understanding local regulatory requirements and cultural peculiarities. Additionally, it investigates best practices and strategies that Ukrainian enterprises can employ for the effective adaptation of their technological products to external markets. The findings of this research can be beneficial for Ukrainian companies seeking to expand their presence in international markets and increase their competitiveness. Results. The findings underscore the significance of strategic product adaptation for Ukrainian enterprises, offering avenues for increased competitiveness, expanded market reach, and sustainable economic growth. By understanding and responding to evolving market dynamics, Ukrainian companies can cultivate stronger international partnerships and drive innovation, thereby contributing to broader economic development objectives. Conclusion. The adaptation of technological products for foreign markets represents a crucial strategic endeavor for Ukrainian enterprises, offering the potential for increased competitiveness, expanded market reach, and sustainable economic growth. Through concerted efforts to understand, anticipate, and respond to evolving market dynamics, Ukrainian companies can forge stronger international partnerships, drive innovation, and contribute to the country's broader economic development objectives.